PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL STATEMENTS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - Mega Indah Lestari; Deliza Henny (Jurnal Akuntansi Trisakti, 2019)
The Objective of this research is to analyze the factors of financial report fraud with pentagon fraud analysis. This research uses six independent variables which is pressure used financial target and financial stability as proxy, opportunity with proxy  ineffective monitoring, rationalization with change in auditor as proxy, capability with proxy of CEO’s education, and arrogance with proxy frequent number of CEO’s picture, while the dependent variable is fraudulent financial statements proxied by restatement of financial statements. This research uses secondary data that is financial report and annual report. The sample of this study is 110 samples from financial statements of financial companies listed in the Indonesia Stock Exchange (BEI) during the 2015-2017 period. Sampling technique used is purposive sampling method. The method of analysis in this study uses logistic regression analysis method.The results of this research shows that the financial stability variable and ineffective monitoring are significant in detecting fraudulent financial statements. While financial targets variable, auditor’s change variable, CEO’s education variable, and frequent number of CEO’s picture are not significant in detecting fraudulent financial statements.